PENANDA SINTAKSIS ATAS DIFERENSIASI HISTORIS DALAM AYAT-AYAT DIALOG MIRIP AL-QUR’AN: Kritik terhadap Pendekatan Sastra Muhammad Ahmad Khalafallah - M. Nurul Huda (AL ITQAN: Jurnal Studi Al-Qur'an, 2025)
This article examines Qur’anic narrative verses that contain similar dialogue formulations in order to clarify historical values often neglected in a literary reading of Qur’anic stories. The main data are QS al-Baqarah: 126 and QS Ibrahim: 35 on Abraham’s supplication, QS al-Baqarah: 35 and QS al-A‘raf: 19 on the command addressed to Adam, QS al-Baqarah: 58 and QS al-A‘raf: 161 on the command addressed to the Children of Israel, and QS Hud: 27 and QS al-Mu’minun: 24 on the dialogue of Noah’s people. This library-based study employs a syntactic approach. The analytical tools include i‘rab, subject-predicate and object relations, indefiniteness and definiteness, the semantic functions of the coordinators wa and fa, demonstratives, pronouns, addressees, and the relationship between sentence structure and the verse context. The findings show that similar dialogue does not necessarily refer to one identical event. Small syntactic differences may indicate different chronological positions, speakers, addressees, and historical contexts. This article criticizes the limitation of Muhammad Ahmad Khalafallah’s literary approach, which tends to prioritize aesthetic and moral functions over historical consideration. The study contributes to Qur’anic interpretation by showing that grammatical analysis can refine the understanding of narrative verses, especially when a purely historical approach faces difficulty in dealing with verses that appear textually similar.